The Relationship between the traditional media and social networking sites from the viewpoint of Active Palestinian journalists in the West Bank and Gaza Strip - Al- Froukh, Mahmoud Fathi (Journal of Humanities & Social Sciences, 2022)
The objective of this study aims mainly to know the relationship between the traditional media and social networking sites from the viewpoint of Active Palestinian journalists in the West Bank and Gaza Strip, and to news to which extent the study sample relied on these sites as a source of news, to achieve the objectives of the study, the reliance on the analytical descriptive approach, a questionnaire was designed and distributed to a random sample of Tow Hundred journalists.The researchers used the SPSS software to verify the validity of the study hypotheses. The study reached a set of results, hence, The study reached a set of results, the most important of which are:-Journalists rely on social media in different degrees, some of whom are always dependent (25%), mostly (40.5%), sometimes (27%), and rarely (5.5%), and some of them do not depend on it at all (2%), while most of them depend on it (98%(.-Political, social and cultural news types are widely obtained from social networking sites.-The most important factors behind the accreditation of journalists to social media sites, as a source of news, are: increasing knowledge and access to the latest local and international developments, accessing materials that are not available in other means, Journalist spend time watching listening and browsing SNS, in addition to entertainment and leisure time.-Social networking sites have spread and expanded at the expense of traditional media, in a transformational relationship.In the light of the findings, the study recommended the need to investigate the credibility of news published on social networking sites from other sources before publishing, legislation, and laws related to freedom of expression are needed; to set standards for publishing news on these sites and to awareness of journalists regarding the risks of distortion and publishing Rumors as news, as well as increased attention to traditional media and work to develop and update it to keep pace with social networking sites.
Keywords: traditional media; social networking sites; Palestinian journalists